Substantiation and analysis of adaptive model of medical-and-social rehabilitation of alcohol dependent persons introduction efficacy - Aimetov, K. V.; Vozny, D. V. (Journal of Education, Health and Sport, 2016)
Aimetov K. V., Vozny D. V. Substantiation and analysis of adaptive model of medical-and-social rehabilitation of alcohol dependent persons introduction efficacy. Journal of Education, Health and Sport. 2016;6(9):1015-1027. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.265663 http://ojs.ukw.edu.pl/index.php/johs/article/view/4214 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. Substantiation and analysis of adaptive model of medical-and-social rehabilitation of alcohol dependent persons introduction efficacy K. V. Aimetov, D. V. Vozny Odessa National Medical University, Ukraine Summary The Authors describe the results of their researches as to implementation of adaptive models of health and social care for alcohol dependent persons. The developed and implemented adaptive systems based on certain factors and realized in a certain clinical establishment with standard technology BRENDA in the presence/ absence of the prolonged pharmacological support are compared. Clinical peculiarities of alcohol dependence and biological, social and psychological factors disrupt remission in alcohol – dependent persons were revealed. To achieve the objectives set, a program included several stages: initial clinical psychological diagnosis, identification of relapses key risk factors of alcohol dependence, implementation of adaptive models of medical and social rehabilitation, and assess the effectiveness of implemented models, creation of proposals for implementation of the proposed adaptive model medical and social rehabilitation were created. Key words: alcohol dependence, adaptive model, and social rehabilitation.